The Relationship between Emotional Intelligence and Cognitive Learning Outcomes of Grade IV Elementary School Students - Dinda Sari Hasibuan, Tenny; Mustika, Dea (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This study aims to investigate the relationship between emotional intelligence and cognitive learning outcomes of fourth grade students at 105 Pekanbaru State Elementary School. Data collection techniques used questionnaires to measure emotional intelligence variables and tests to measure cognitive learning outcomes. Data analysis was conducted using prerequisite tests, including normality and linearity tests, followed by hypothesis testing using simple linear regression and calculation of the coefficient of determination. The results showed that there was a positive and significant relationship between emotional intelligence and students' cognitive learning outcomes (significance value = 0.006). The coefficient of determination (R²) of 0.267 indicates that emotional intelligence contributes 26.7% to the variation in cognitive learning outcomes, while the remaining 73.3% is influenced by other factors not examined in this study. The findings provide important implications for education in considering the development of emotional intelligence as a factor that can improve students' cognitive learning outcomes at the primary school level